Sosialisasi Kesehatan Ramadhan Sehat Puasa Nikmat - Siti Latipah; Shieva Nur Azizah Ahmad; Ika Oktaviani (Jurnal Abdimas Kesehatan (JAK), 2023)
Requiring children to fast is not immediate or spontaneous, but rather provides habituation training first, because fasting is not only fighting against lust, but you have to get used to waking up early in the morning for sahur when the child is sound asleep. The aim of community service activities is to increase knowledge about the health of fasting in the community. The month of Ramadan for children at the Shaleh Idris Children's Center Foundation. This activity will be held on Saturday, April 8, 2023 for 60 minutes. There were 30 participants in the activity for orphaned children aged 8-13 years. The activity was carried out at the Bumi Agung Permai 2 Housing Complex, Serang City, Banten. The activity was carried out by providing equipment for 30 minutes, followed by discussion and questions and answers. At the end of the activity, quizzes and door prizes are given to participants. In this activity, a pre-test and post-test were carried out as an evaluation of the activity. The results of the pre-test and post-test show that there is a significant increase in knowledge in the good category by 90% and in the poor category by 10%. Knowledge about healthy fasting given during childhood will increase awareness and internalize it in them until they grow up, so they can behave in a healthy way